Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 27. Beitrag: Hymenoptera: Apidae I (Xylocopinae). - Atanassov, Neno (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The above publication deals with the Xylocopinae collected by the expedition of the Deutsches Entomologisches Institut to Albania including the records of Xylocopinae from this areal on the literature. The expedition collected 42 specimens of 3 species: Xylocopa violacea L., X. valga Gerstäcker, and X. cyanescens Brulle. Another one mentioned by Maidl (1922) from Albania is X. olivieri Lepeletier.